Medicinal prospects of antioxidants from algal sources in cancer therapy - Ferdous, Umme Tamanna; Balia Yusof, Zetty Norhana (Frontiers Media, 2021)
Though cancer therapeutics can successfully eradicate cancerous cells, the effectiveness of these medications is mostly restricted to several deleterious side effects. Therefore, to alleviate these side effects, antioxidant supplementation is often warranted, reducing reactive species levels and mitigating persistent oxidative damage. Thus, it can impede the growth of cancer cells while protecting the normal cells simultaneously. Moreover, antioxidant supplementation alone or in combination with chemotherapeutics hinders further tumor development, prevents chemoresistance by improving the response to chemotherapy drugs, and enhances cancer patients’ quality of life by alleviating side effects. Preclinical and clinical studies have been revealed the efficacy of using phytochemical and dietary antioxidants from different sources in treating chemo and radiation therapy-induced toxicities and enhancing treatment effectiveness. In this context, algae, both micro and macro, can be considered as alternative natural sources of antioxidants. Algae possess antioxidants from diverse groups, which can be exploited in the pharmaceutical industry. Despite having nutritional benefits, investigation and utilization of algal antioxidants are still in their infancy. This review article summarizes the prospective anticancer effect of twenty-three antioxidants from microalgae and their potential mechanism of action in cancer cells, as well as usage in cancer therapy. In addition, antioxidants from seaweeds, especially from edible species, are outlined, as well.